Применение препарата Тригамма® в лечении заболеваний нервной системы - Е. А. Широков; А. А. Михайлов (Архивъ внутренней медицины, 2011)
The article discusses the questions of usage of the drug Trigamma® as a therapy of patients with lesions of the nervous system as well as some other diseases based on the experience of Russian and foreign experts. The advantages of the drug Trigamma® are based on a balanced composition, and synergistic action of its components. We consider the therapeutic potential of Trigammа® and the possibilities to prescribe it to a wide range of patients as an effective, highly secure, affordable and easy-to-use drug.